KEWENANGAN HUKUM PEMERINTAH DAERAH DALAM STANDARISASI PANGAN PROGRAM MAKANAN BERGIZI: KAJIAN KASUS KERACUNAN MASSAL DI KOTA BOGOR: Legal Authority Of Local Government In Food Standardization For Nutritious Meal Program: Case Study In Bogor City - Putri Aulia Ramadhan; Ali Rido (Reformasi Hukum Trisakti, 2026)
Indonesia bears a constitutional responsibility to ensure access to nutritious food as part of mandatory basic public services under Law No. 23 of 2014 on Regional Government. In practice, the implementation of the Free Nutritious Meal Program (MBG) on Bogor City has shown significant vulnerability to failures in food standardization, as evidenced by a mass food poisoning incident affecting 223 students on May 2025. This study examines the implementation of local government legal obligations and the factor hindering their effectiveness, particularly regulatory gaps. The research employs normative legal methods using statutory and case-based approaches, analyzed through descriptive-prescriptive techniques. The findings indicate that legal protection provided by the local government through the mayor and relevant local regulations governing food standardization. The study concludes that efforts to ensure food standardization in the MBG program are not yet optimal, highlighting the need for strengthened local policies, improved institutional coordination, and effective use of mayoral regulatory authority to achive sustainable legal protection